Evaluation of Two New Indices of Blood Pressure Variability Using Postural Change in Older Fallers. Issue 19 (May 2016) - Goh, Choon-Hian; Ng, Siew-Cheok; Kamaruzzaman, Shahrul B.; Chin, Ai-Vyrn; Poi, Philip J. H.; Chee, Kok Han; Imran, Z. Abidin; Tan, Maw Pin
Abstract : Abstract: To evaluate the utility of blood pressure variability (BPV) calculated using previously published and newly introduced indices using the variables falls and age as comparators. While postural hypotension has long been considered a risk factor for falls, there is currently no documented evidence on the relationship between BPV and falls. A case-controlled study involving 25 fallers and 25 nonfallers was conducted. Systolic (SBPV) and diastolic blood pressure variability (DBPV) were assessed using 5 indices: standard deviation (SD), standard deviation of most stable continuous 120 beats (staSD), average real variability (ARV), root mean square of real variability (RMSRV), and standard deviation of real variability (SDRV). Continuous beat-to-beat blood pressure was recorded during 10 minutes' supine rest and 3 minutes' standing. Standing SBPV was significantly higher than supine SBPV using 4 indices in both groups. The standing-to-supine-BPV ratio (SSR) was then computed for each subject (staSD, ARV, RMSRV, and SDRV). Standing-to-supine ratio for SBPV was significantly higher among fallers compared to nonfallers using RMSRV and SDRV ( P  = 0.034 and P  = 0.025). Using linear discriminant analysis (LDA), 3 indices (ARV, RMSRV, and SDRV) of SSR SBPV provided accuracies of 61.6%, 61.2%, and 60.0% for the prediction of falls which is comparable with timed-up and go (TUG), 64.4%. This study suggests that SSR SBPV using RMSRV and SDRV is a potential predictor for falls among older patients, and deserves further evaluation in larger prospective studies.